2016
DOI: 10.3945/ajcn.115.126375
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in human milk leptin and insulin are associated with early changes in the infant intestinal microbiome

Abstract: Our results indicate that, although maternal obesity may adversely affect the early infant intestinal microbiome, HM insulin and leptin are independently associated with beneficial microbial metabolic pathways predicted to increase intestinal barrier function and reduce intestinal inflammation. This trial was registered at clinicaltrials.gov as NCT01693406.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 68 publications
10
117
0
Order By: Relevance
“…Gammaproteobacteria are a major source of LPS and are considered transient pioneering bacteria important for developing endotoxin tolerance and protection against excessive inflammatory and autoimmune gastrointestinal disorders later in life 132134 . A statistically significant 50% reduction in Gammaproteobacteria abundance was found in stool of 2weekold babies born to mothers with obesity, along with increased levels of acetate 135 , which promotes hepatic de novo lipogenesis and NAFLD. We have transferred gut microbes from infants born to mothers who are obese into germfree mice; these mice showed signs of elevated cytokines in portal blood and liver endoplasmic reticulum stress (increased gene expression of spliced Xbp1 ) when compared with mice colonized with stool from babies born to mothers of a normal weight (J. E. Friedman, unpublished work).…”
Section: Early Postnatal Factorsmentioning
confidence: 99%
“…Gammaproteobacteria are a major source of LPS and are considered transient pioneering bacteria important for developing endotoxin tolerance and protection against excessive inflammatory and autoimmune gastrointestinal disorders later in life 132134 . A statistically significant 50% reduction in Gammaproteobacteria abundance was found in stool of 2weekold babies born to mothers with obesity, along with increased levels of acetate 135 , which promotes hepatic de novo lipogenesis and NAFLD. We have transferred gut microbes from infants born to mothers who are obese into germfree mice; these mice showed signs of elevated cytokines in portal blood and liver endoplasmic reticulum stress (increased gene expression of spliced Xbp1 ) when compared with mice colonized with stool from babies born to mothers of a normal weight (J. E. Friedman, unpublished work).…”
Section: Early Postnatal Factorsmentioning
confidence: 99%
“…Breast milk from overweight and obese mothers has been reported to have higher levels of insulin and leptin, lower levels of omega-3 PUFA, and higher omega-6:omega-3 PUFA ratios, 153 while showing no differences in macronutrient composition. [154][155][156] Immunological modulators transforming growth factor β2 and sCD-14 have also been reported to be lower in breast milk from obese women. 157 Several other hormones and cytokines present in milk have as yet uncharacterized biological effects on the gastrointestinal and immune systems of the offspring.…”
Section: Alterations In Neonatal Nutrition and Infant Microbiomementioning
confidence: 99%
“…More recently, the microbiome of exclusively breastfed infants from lean and obese women was characterized at 2 weeks of age. 156 These studies showed that both maternal obesity status and milk insulin concentrations were associated with early changes in the infant's microbiome. The persistence of the changes in later life remains to be ascertained.…”
Section: Alterations In Neonatal Nutrition and Infant Microbiomementioning
confidence: 99%
“…We have recently shown in a prospective study on vaginally-delivered, exclusively breastfed infants with no neonatal or postnatal exposure to antibiotics that neonates born to mothers with obesity showed a significant 50% reduction in Gammaproteobacteria at 2 weeks of age compared with infants of normal-weight mothers (Lemas et al 2016). A striking relative depletion in Proteobacteria species was recently found in 2-day-old neonates delivered vaginally, but not by cesarean section, to overweight/obese mothers (Mueller et al 2016), suggesting the differences in relative abundance of Gram-negative bacteria may stem from vertical transmission of the maternal microbiota.…”
Section: The Importance Of Proteobacteria To Immune Education In Earlmentioning
confidence: 99%